Precision and reliability of the polar team pro computer software for analyzing heart rate variability - Perrotta, A. S.; Day, B. D.; Scott, A. J.; Gnatiuk, E. A. (Sports Engineering, 2023)
The Polar Team Pro computer software program simultaneously analyzes heart rate variability (HRV) for multiple athletes and requires little to no expertise from the user. Still, there remains the need to examine the accuracy and reliability of this candidate software when compared to the recognized gold standard HRV computer software program (Kubios HRV). Twenty-one (n = 21) healthy female soccer players volunteered to be participants. An ultra-short recording period (60-s) of R-R intervals (ms) was collected in the supine position in a controlled laboratory setting over two data collection periods spaced one month apart. R-R intervals were exported into both the candidate and reference computer software for analysis. The root mean square of the successive differences (rMSSD) were calculated along with mean R-R interval length. rMSSD values derived from the candidate software were compared to both the raw and artefact corrected values from the reference software. After performing artefact correction, mean (± SD) rMSSD values were not statistically different between software (candidate = 61.2 ± 31.0 ms `vs` reference = 63.1 ± 31.1 ms, p = 0.214). Mean (± SD) R-R intervals were significantly different (candidate = 893.4 ± 119.8 ms `vs` reference = 882.3 ± 111.3 ms, p = 0.003). Excellent reliability in artefact corrected rMSSD (r = 0.95, p < 0.001) and mean R-R interval length (r = 0.99, p < 0.001) was observed. The candidate software showed strong agreement and excellent reliability in calculating rMSSD when compared to the gold standard after artefact correction was applied.